Existence Theory and Stability Analysis of Nonlinear Neutral Pantograph Equations via Hilfer-Katugampola Fractional Derivative - S. Harikrishnan; E.M. Elsayed; K. Kanagarajan (Journal of Advances in Applied & Computational Mathematics, 2020)
The aim and objectives of this paper are devoted to study some adequate results for the existence and stability of solutions of nonlinear neutral pantograph equations with Hilfer-Katugampola fractional derivative. The arguments are based upon Schauder fixed point theorem and Banach contraction principle. Further, we also study the Ulam type stability for proposed problem.